The 2D‐directed spanning forest is almost surely a tree. Issue 1 (5th February 2012) - Coupier, David; Tran, Viet Chi
Abstract We consider the Directed Spanning Forest (DSF) constructed as follows: given a Poisson point process N on the plane, the ancestor of each point is the nearest vertex of N having a strictly larger abscissa. We prove that the DSF is actually a tree. Contrary to other directed forests of the literature, no Markovian process can be introduced to study the paths in our DSF. Our proof is based on a comparison argument between surface and perimeter from percolation theory. We then show that this result still holds when the points of N belonging to an auxiliary Boolean model are removed. Using these results, we prove that there is no bi‐infinite paths in the DSF. © 2012 Wiley Periodicals, Inc. Random Struct. Alg., 2012